2012
DOI: 10.1159/000345079
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Vertebrobasilar Artery Morphology between Spontaneous Intradural Vertebral Artery Dissections with and without Subarachnoid Hemorrhage

Abstract: Background: Patients with spontaneous intradural vertebral artery dissection (siVAD) developing subarachnoid hemorrhage (SAH) have been observed to have poor outcomes. Factors predisposing siVAD patients to SAH are not well known. We aimed to investigate the clinical and vertebrobasilar artery morphological characteristics associated with SAH in patients with siVAD. Methods: We reviewed 103 consecutive patients with siVAD managed at our facility between July 2003 and June 2012. We divided the patients into gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 69 publications
1
14
0
Order By: Relevance
“…Hence, the present method is effective for measuring the degree of angulation of the BA quantitatively. Previous methods for analyzing BA geometry were largely dependent on 2D axial images (XY sections only) 25,26) or maximum intensity projection (MIP) images 9,16,27) . However, the geometry of the BA cannot be measured appropriately using previous conventional methods for the following reasons: 1) the reference points frequently overlap and are obscured, and 2) the BA angles and distances are measured on randomly projected images, especially when using MIP images.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, the present method is effective for measuring the degree of angulation of the BA quantitatively. Previous methods for analyzing BA geometry were largely dependent on 2D axial images (XY sections only) 25,26) or maximum intensity projection (MIP) images 9,16,27) . However, the geometry of the BA cannot be measured appropriately using previous conventional methods for the following reasons: 1) the reference points frequently overlap and are obscured, and 2) the BA angles and distances are measured on randomly projected images, especially when using MIP images.…”
Section: Discussionmentioning
confidence: 99%
“…16,44 The relative frequency of intracranial artery dissections in the diff erent intracranial segments varies between studies (table 1; appendix), but in most series the vertebral artery (intradural portion [V4 segment]) is the most common site. Bilateral intracranial artery dissection seems to happen less often than bilateral cervical artery dissection does (<11% in most intracranial artery dissection series 21,30,32,34 vs 15% in cervical artery dissection series 11,17,45 ), with bilateral intracranial artery dissection mostly reported in the V4 segment.…”
Section: Epidemiologymentioning
confidence: 92%
“…Recurrent bleeding was reported in 0-11% of patients with intracranial artery dissection with subarachnoid haemorrhage after surgical or endovascular treatment, and after treatment for ischaemia in 0-22% of patients. 19,[21][22][23][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Cranial nerve palsies and spinal cord infarctions were seldom reported. 35,41,93 Overall, of 813 endovascular procedures, 50 (6•2%) cerebral or spinal cord ischaemia, 15 (1•8%) rupture and rebleeding, and seven (0•9%) cases of cranial nerve palsies were reported; of 125 surgical procedures, 23 (18•4%) cerebral or spinal cord ischaemia, one (0•8%) rupture and rebleeding, and one (0•8%) case of cranial nerve palsy were reported.…”
Section: Review Surgical and Endovascular Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Our recent studies showed that some vertebrobasilar morphologies might have an influence on siVAD-induced subarachnoid haemorrhage 8 9. We hypothesised that vertebrobasilar morphologies might also be markers for unruptured siVAD instability, leading to the signs of siVAD progression, including siVAD-induced stroke or worsening of aneurysmal dilatation and stenotic occlusive changes.…”
Section: Introductionmentioning
confidence: 96%